Quantum chemical investigation of spectroscopic studies and hydrogen bonding interactions between water and methoxybenzeylidene-based humidity sensor - Muhammad, Shabbir; Irfan, Ahmad; Al-Sehemi, Abdullah G.; Al-Assiri, M. S.; Kalam, Abul; Chaudhry, Aijaz R. (Journal of Theoretical and Computational Chemistry, 2015)
A quantum chemical investigation has been performed to spotlight the structure–property relationship among methoxybenzeylidene-based humidity sensor and water molecules. The chemical interactions among (E)-2-(4-(2-(3,4-dimethoxybenzeylidene)hydrazinyl)phenyl) ethane-1,1,2-tricarbonitrile (DMBHPET) sensor and water molecules have been studied using density functional theory (DFT) methods. The molecular structural parameters, binding energies and Infrared (IR) spectroscopic analyses have been performed to assess the nature of intermolecular interactions. Three different positions have been identified for possible attachments of H2O molecules through hydrogen bonding interactions. These positions include NH (complex 1a), p-OCH3 (complex 1b) and N=N (complex 1c) group in sensor molecule (1) for the chemical adsorption of water molecules. While, the complex 1abc includes all three sites with simultaneously three H2O molecules attached to it through hydrogen bonding. The binding energies calculated for complex 1a(NH…H2O), complex 1b(CH3O…H2O), complex 1c(N=N…H2O) and complex 1abc are -30.97, -18.41, -13.80 and -65.36 kcal/mol, respectively. The counterpoise (CP) scheme has been used to correct the basis set superposition error (BSSE) in calculation of binding energies of sensor and H2O complexes. The higher binding energy of -65.36 kcal/mol for complex 1abc represents that the present methoxybenzeylidene-based sensor has significant potential through hydrogen bonding formation for sensing humidity as indicated in our previous experimental investigation. The evidence of hydrogen bonding interactions between sensor 1 and H2O molecules has been traced through structural parameters, red shift in IR spectra as well as molecular electrostatic maps. Thus the present investigation highlights the first computational framework for a molecular level structure-binding activity of a methoxybenzeylidene-based sensor and water molecules. Using state-of-art computational methods, we have presented a first theoretical framework to limelight the hydrogen bonding interactions among water and humidity sensing molecules. The sensing of humidity molecules has been simulated and efficiency of sensor has been investigated in terms of structural parameters, binding affinity and vibrational spectroscopic outcomes. The calculated binding energy of –65.36 kcal/mol among sensor and water molecules is relatively large enough to make it suitable as potential candidate for humidity sensing.